ChemInform Abstract: Diastereoselective Radical Hydroacylation of Alkylidenemalonates with Aliphatic Aldehydes Initiated by Photolysis of Hypervalent Iodine(III) Reagents. Issue 40 (September 2016) - Selvakumar, Sermadurai; Sakamoto, Ryu; Maruoka, Keiji
Abstract: The mild, metal‐free reaction delivers chiral ketones in a highly diastereoselective manner.